GILTERITINIB (XOSPATA ®) IN TURKEY: EARLY ACCESS PROGRAM RESULTS - Mehmet Hilmi DOGU; Ali Irfan Emre TEKGUNDUZ; Burak DEVECI; Gulten KORKMAZ; Melda COMERT; Omur Gokmen SEVINDIK; Osman YOKUS; Istemi SERIN (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Background: Gilteritinib (XOSPATA ®, Astellas) is a type I oral FLT3 inhibitor, a tyrosine kinase AXL inhibitor involved in both c-Kit and FMS-like tyrosine kinase 3 (FLT3) resistance. In the phase 3 ADMIRAL trial, gilteritinib was compared with the standard of care in (R/R) acute myeloid leukemia (AML) patients who harbored any FLT3 mutation and showed superior efficacy with regard to response and survival. Objectives: The purpose of this research was to investigate the real-life efficacy and safety of gilteritinib in FLT3-positive R/R AML patients who were treated as a part of an early access program that was held in Turkey starting in April 2020 (NCT03409081). Results: The research included 17 R/R AML patients who had received gilteritinib from a total of 7 centers. The most common adverse events were anemia and hypokalemia (7 patients, 41.2%). Grade 4 thrombocytopenia was observed in only one patient (5.9%), which led to permanent discontinuation of treatment. The overall response rate was 100%. Patients with peripheral edema had a 10.47 (95% CI: 1.64-66.82) times higher risk of death than those without peripheral edema (p<0.05). Conclusion: This research showed that patients with febrile neutropenia and peripheral edema were at a high risk of death when compared to patients without febrile neutropenia and peripheral edema.